Implementasi Math Clinic Dalam Meningkatkan Kemampuan Matematis Siswa Dengan System Pembelajaran Hibryd - Nainggolan, Arisan Candra; Sitepu, Israil (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
The sudden appearance of Covid-19, which has disrupted the stability of almost all lines of life on earth, has now begun to subside. The learning and teaching process in schools has also entered the new normal, even face-to-face learning has been 100% enforced. However, the war between Russia and Ukraine which is still going on today has had a negative impact on the global economy. Globally, the war in Ukraine is a "disaster" for the world that will reduce global economic growth. The government has also increased the price of fuel oil (BBM) in our country. This of course will have an impact on rising prices of goods, including the price of basic necessities. The impact of the increase in the prices of these necessities will make it difficult for the people's economy, especially the middle to lower economic community. The people who live in Rorinata Housing Phase X, Hamlet IV, Suka Maju Village, Kec. Sunggal Deli Serdang Regency is a community with a middle to lower economy. This of course will indirectly affect the ability of parents of students who live in the housing to pay for additional learning for their children. Or in other words, students' parents will find it difficult to pay for additional tutoring for their children. One way to overcome this problem is through the Mathematics Clinic (Math Clinic Program). The application of the Math Clinic with the Hybrid Learning System has been able to help and improve the mathematical abilities of students who live in Phase X Rorinata Housing, Hamlet IV, Suka Maju Village, Kec. Sunggal Deli Serdang Regency.